Frontiers in Algorithmics: 10th International Workshop, FAW 2016, Qingdao, China, June 30- July 2, 2016, Proceedings - Zhu, Daming; Bereg, Sergey (Lecture Notes in Computer Science, 2016)
This book constitutes the proceedings of the 10th International Workshop on Frontiers in Algorithmics, FAW 2016, held in Qingdao, China, in June/July 2016.      The 25 full papers presented in this volume were carefully reviewed and selected from 54 submissions. They deal with algorithm, complexity, problem, reduction, NP-complete, graph, approximation, linear programming, local search, integer programming, semidefinite programming, parameterized algorithm, fixed parameter, tractability, randomness, computational geometry.